2018
DOI: 10.1093/trstmh/try017
|View full text |Cite
|
Sign up to set email alerts
|

Backyard pigs are a reservoir of zoonotic hepatitis E virus in southern Brazil

Abstract: MF438128-MF438135.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…According to Cleaveland et al (2001), 77% of pathogens from livestock animals can infect multiple hosts. Swine species can act as reservoirs of many other pathogens, including hepatitis E virus, Streptococcus suis, and Taenia solium (Da Silva et al, 2018;Chu et al, 2019). Livestock and domestic animals can also transmit pathogens to wild species (Mahapatra et al, 2015;Bevins et al, 2018).…”
Section: Animal Host-associated Factorsmentioning
confidence: 99%
“…According to Cleaveland et al (2001), 77% of pathogens from livestock animals can infect multiple hosts. Swine species can act as reservoirs of many other pathogens, including hepatitis E virus, Streptococcus suis, and Taenia solium (Da Silva et al, 2018;Chu et al, 2019). Livestock and domestic animals can also transmit pathogens to wild species (Mahapatra et al, 2015;Bevins et al, 2018).…”
Section: Animal Host-associated Factorsmentioning
confidence: 99%
“…In pigs from family-scale the anti-HEV IgG prevalence was 0% [ 61 ] and 67% [ 60 ] in the Midwest region, and 77.6% in the South region [ 71 ]. Regarding the detection of HEV RNA in stools of pigs from family-scale farms, 8% [ 61 ] and 24% [ 62 ] were found positive in the Midwest region, and 20% [ 68 ] in the South region.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the molecular characterization of HEV strains detected in Brazil, studies showed that all HEVs found in Brazil were classified as HEV-3 (6 studies in humans, 15 in swine and animal products, and 2 on environmental samples). HEV-3 is known to have a zoonotic (swine) origin and the subtypes 3b and 3i were detected in humans [33,40,45] and pigs [61,62,65,66,[68][69][70][71][72], while the subtypes 3c [57,65,71], subtype 3d [61], subtype 3f [57,58,62] and subtypes 3h [61,71] have been only detected in pigs. As molecular studies have been performed using several molecular assays and primer choices, different regions of HEV have been targeted and characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For much of recorded history, humans have farmed these animals in traditional ways, keeping just enough animals for personal or family consumption ( Salaheen et al, 2015 ). In these traditional systems, while humans are exposed to zoonotic pathogens because of possible introduction of pathogens from wildlife and intimate contact with animals ( Pohjola et al, 2016 ; da Silva et al, 2018 ; Nicholson et al, 2020 ), the impact of such zoonotic transmission is limited by the small numbers of these animals ( Espinosa et al, 2020 ).…”
Section: Introduction Of Concentrated Animal Feeding Operationsmentioning
confidence: 99%